THE IMPACT OF AN EDUCATIONAL PROGRAM ACCORDING TO THE VARK MODEL USING AUXILIARY MEANS ON THE ACCURACY OF FENCING - Asst. Prof. Dr. Mohammad Dia Abdul Rasul; Asst. Lect. Bashaer Harbi Ouda; Asst. Lect. Noor Saad Abdulhameed (Galaxy International Interdisciplinary Research Journal, 2024)
The importance of the research lies in developing an educational program for the skill of fencing according to the VARK model at the training center for fencing in Al-Muthanna Governorate, and providing Iraqi trainers with the importance of using this model, which is considered one of the modern patterns in learning the technical performance of the skill that should be emphasized when developing educational programs under conditions that are suitable for fencing sport. This is to benefit from it during its application by those working on it, as the research problem was that most trainers in training centers provide training units that lack educational units that are inconsistent with the kinesthetic learning process and its various patterns. They start giving educational units late in the learner’s life, contrary to what is seen in advanced countries where they provide the skill to the learner at an early age using modern and different methods and patterns that help in the learning process of the skill in a way that makes it easier for the learner to memorize and recall the skill. Therefore, the researchers saw the use of the VARK model in improving the learning process, which is one of the important stages in the kinesthetic learning process, as it is one of the modern methods in the learning process, and moving away from traditional patterns that limit the training age for the learner. The research aimed to prepare an educational program according to the VARK model using assistive means in the accuracy of fencing among saber fencers and to identify the impact of the educational program according to the VARK model using assistive means in the accuracy of fencing among saber fencers in Al-Muthanna Governorate. The research hypotheses were that there are statistically significant differences between the control group and the experimental group in favor of the experimental group as a result of using educational means according to the VARK model in the accuracy of fencing among saber fencers.